Porter’s Generic Competitive Strategies, Alliance Partnerships and Firm Performance of Mobile Telephone Network Service Providers in Kenya - Musyoka, Margret; Arasa, Robert; Ombuki, Charles (European Journal of Business and Strategic Management, 2022)
Purpose: The aim of the study was to investigate on focus strategy, partnership alliances and firm performance of mobile telephone network service providers in Kenya. Methodology: The study used positivism research philosophy and descriptive research design methodology. The target population was all the 66 mobile telephone network service providers in Kenya. Primary data was gathered through use of structured questionnaires. Descriptive statistics, correlation and regression modeling was used to aid in data analysis. Findings: Descriptive analysis portrayed that the 61 mobile telephone network service providers in Kenya registered had increased returns with a composite score of 3.84. Hierarchical regression results portrayed that partnership alliances moderated the relationship between focus strategy and performance of mobile telephone network service providers in Kenya as far as Equity Alliance component is concerned with (p value of .04) which is less than the critical value (.05). Franchises, Diagonal alliances, Focus Strategy, Vertical alliances, Joint Ventures, Equity alliances, and Horizontal alliances had no statistically significant moderating effect. Unique contribution to theory, practice and policy: Generally, firms should consider partnership alliances as a conditional factor in the relationship between focus strategy and firm performance other than treating it as a pure predictor. Further, the management of mobile telephone network service providers in Kenya should consider the extent to which individual components of partnership alliances moderate Porters' competitive strategies to performance linkage. On the other hand, the current study is possibly the first of its kind in making distinct involvement of strategic management knowledge frontiers. This was achieved through harmonizing and endorsing the hypotheses of the three theories that while Porter's generic differentiation strategy significantly influence performance of mobile telephone network service providers in Kenya, the moderating effect of alliance partnerships gives a more comprehensive explanation to management as to why many such firms prefer the alliance partnerships instead of an apparent increase in profitability caused by the porter's strategic moves. That is, the Resource Based View Theory, syncretic paradigm theory and transaction cost theory have received an empirical support through this study for the theories are relevant to strategic decisions other than the Porters ones which affects the overall business objectives. Therefore, the three theories are significant to the current study since they alert managers to contrast in-house transaction costs with outdoor costs before choosing to execute inside or without.